On Efficiency of Parallel Solvers for the Blood Flow through Aortic Valve - Starikovičius, Vadimas; Kačeniauskas, Arnas; Maknickas, Algirdas; Stupak, Eugeniuš; Pacevič, Ruslan; Staškūnienė, Miglė; Davidavičius, Giedrius (Mathematical Modelling and Analysis, 2017)
Mathematical modelling of cardiac haemodynamics presents a great challenge to the computational scientists due to numerous numerical issues and required computational resources. In this paper, we study the parallel performance of 3D simulation software for the blood flow through the aortic valve. The fluid flow problem with the open aortic valve leaflets is formulated and solved in parallel. The choice between the segregated and coupled numerical schemes is discussed and investigated. We present and compare the parallel performance results of both types of parallel solvers. We investigate their strong and weak scalability.